Generation and characterization of large-particle aerosols using a center flow tangential aerosol generator with a non-human-primate, head-only aerosol chamber. (April 2015) - Bohannon, J. Kyle; Lackemeyer, Matthew G.; Kuhn, Jens H.; Wada, Jiro; Bollinger, Laura; Jahrling, Peter B.; Johnson, Reed F.
Abstract Aerosol droplets or particles produced from infected respiratory secretions have the potential to infect another host through inhalation. These respiratory particles can be polydisperse and range from 0.05 to 500 µm in diameter. Animal models of infection are generally established to facilitate the potential licensure of candidate prophylactics and/or therapeutics. Consequently, aerosol-based animal infection models are needed to properly study and counter airborne infections. Ideally, experimental aerosol exposure should reliably result in animal disease that faithfully reproduces the modeled human disease. Few studies have been performed to explore the relationship between exposure particle size and induced disease course for infectious aerosol particles. The center flow tangential aerosol generator (CenTAG™) produces large-particle aerosols capable of safely delivering a variety of infectious aerosols to non-human primates (NHPs) within a Class III Biological Safety Cabinet (BSC) for establishment or refinement of NHP infectious disease models. Here, we report the adaptation of this technology to the Animal Biosafety Level 4 (ABSL-4) environment for the future study of high-consequence viral pathogens and the characterization of CenTAG™-created sham (no animal, no virus) aerosols using a variety of viral growth media and media supplements.